Associations Between Wildfire‐Related PM2.5 and Intensive Care Unit Admissions in the United States, 2006–2015. (4th May 2021) - Sorensen, Cecilia; House, John A.; O'Dell, Katelyn; Brey, Steven J.; Ford, Bonne; Pierce, Jeffrey R.; Fischer, Emily V.; Lemery, Jay; Crooks, James L.
Abstract: Wildfire smoke is a growing public health concern in the United States. Numerous studies have documented associations between ambient smoke exposure and severe patient outcomes for single‐fire seasons or limited geographic regions. However, there are few national‐scale health studies of wildfire smoke in the United States, few studies investigating Intensive Care Unit (ICU) admissions as an outcome, and few specifically framed around hospital operations. This study retrospectively examined the associations between ambient wildfire‐related PM2.5 at a hospital ZIP code with total hospital ICU admissions using a national‐scale hospitalization data set. Wildfire smoke was characterized using a combination of kriged PM2.5 monitor observations and satellite‐derived plume polygons from National Oceanic and Atmospheric Administration's Hazard Mapping System. ICU admissions data were acquired from Premier, Inc. and encompass 15%–20% of all U.S. ICU admissions during the study period. Associations were estimated using a distributed‐lag conditional Poisson model under a time‐stratified case‐crossover design. We found that a 10 μg/m 3 increase in daily wildfire PM2.5 was associated with a 2.7% (95% CI: 1.3, 4.1; p  = 0.00018) increase in ICU admissions 5 days later. Under stratification, positive associations were found among patients aged 0–20 and 60+, patients living in the Midwest Census Region, patients admitted in the years 2013–2015, and non‐Black patients, though other results were mixed. Following a simulated severe 7‐day 120 μg/m 3 smoke event, our results predict ICU bed utilization peaking at 131% (95% CI: 43, 239; p < 10 −5 ) over baseline. Our work suggests that hospitals may need to preposition vital critical care resources when severe smoke events are forecast. Plain Language Summary: Wildfire smoke negatively affects people's health. Heavy smoke has been linked to higher rates of hospital admissions, emergency room, admissions, and death. However, we do not know the impact of smoke on Intensive Care Unit (ICU) admissions or on limited hospital resources like ICU beds. To fill this knowledge gap, we linked hospital ICU admissions to smoke levels near those hospitals. We also predicted how many ICU admissions would occur during a simulated severe week‐long smoke event and how many ICU beds would be needed to care for the patients. We found that the link between smoke and ICU admissions was relatively modest, but a severe smoke event could more than double the number of ICU beds needed. Key Points: Associations between smoke PM2.5 and ICU admissions were estimated using a national‐scale cohort Smoke PM2.5 was associated with modest changes in ICU admissions A simulated smoke wave was found to impose severe strain on ICU resources